1996
DOI: 10.1007/bf01253956
|View full text |Cite
|
Sign up to set email alerts
|

Sequence comparisons of the internal transcribed spacer region of ribosomal genes support close relationships between parasitic ants and their respective host species (Hymenoptera: Formicidae)

Abstract: SummaryA fragment of the internal transcribed spacer (ITS-l) adjacent to the 5.8S rRNA gene of 20 myrmicine ant species was sequenced. Sequence comparisons were carried out between 11 species of the tribe Leptothoracini, five species of the tribe Tetramoriini, three species of the tribe Solenopsidini and one species of the tribe Myrmicini. Additionally, the formicine ant Camponotus ligniperda (tribe Camponotini) was analyzed as an outgroup species. Among all investigated species, the fragment had a variable le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
(31 reference statements)
2
27
0
Order By: Relevance
“…Evolutionary rates of the enzyme loci appear very high compared to their Tetramorium hosts. This is particularly surprising in light of the low di vergence of ITS-1 sequences in this group (Baur et al, 1996). A number of studies have shown that rates of mo lecular evolution vary considerably among hosts and parasites belonging to different taxonomic groups (e.g.…”
Section: T Schneideřimentioning
confidence: 84%
See 3 more Smart Citations
“…Evolutionary rates of the enzyme loci appear very high compared to their Tetramorium hosts. This is particularly surprising in light of the low di vergence of ITS-1 sequences in this group (Baur et al, 1996). A number of studies have shown that rates of mo lecular evolution vary considerably among hosts and parasites belonging to different taxonomic groups (e.g.…”
Section: T Schneideřimentioning
confidence: 84%
“…6). First, two shared-derived base substitutions in the ITS-1 and 5.8S rRNA sequences have been reported by Baur et al (1996). Secondly, both Anergates and Teleutomyrmex have developed a very similar form of workerless parasit ism including manifold adaptations, such as physogastry, reduced mouthparts and specialized males (Kutter, 1969;Bolton, 1976).…”
Section: T Schneideřimentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it could explain how the social parasite A. insinuator could have evolved from its host, A. echinatior (Bekkevold and Boomsma, 2000;Schultz et al, 1998) by sympatric speciation. The close phylogenetic affiliation of ant social parasites and their hosts (Schultz et al, 1998) is known as ÔEmeryÕs ruleÕ (Baur et al, 1995(Baur et al, , 1996Buschinger, 1986) and while sympatric speciation is often invoked to explain this pattern (Baur et al, 1995(Baur et al, , 1996Buschinger, 1986), it hard to see how it could arise in the absence of a clear mechanism. Incompatibility between multiple Wolbachia types within a population could provide such a mechanism (Hurst and Schilthuizen, 1998;Stouthamer et al, 1999;Werren, 1998).…”
Section: Discussionmentioning
confidence: 99%